2021
DOI: 10.1017/s0967199420000787
|View full text |Cite
|
Sign up to set email alerts
|

Collection and in vitro maturation of Mazama gouazoubira (brown brocket deer) oocytes obtained after ovarian stimulation

Abstract: Summary In vitro production of embryos has gained prominence as a tool for use in wildlife conservation programmes in situ and ex situ. However, the development of this technique depends on steps that include ovarian stimulation, collection and oocyte maturation. The purpose of this study was to assess the feasibility of an ovarian stimulation protocol for follicular aspiration, the efficiency of videolaparoscopy for follicular aspiration and test a medium for in vitro oocyte maturation for the species Maza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In this species, it was observed that during the estrous season, the best IVM medium was supplemented with 10 μg/mL FSH, 1 μg/mL LH, 0.2 mM cysteamine, and 50 ng/mL EGF, while in the anestrous season, double these concentrations was more efficient (Yin et al, 2012). Additionally, based on the findings observed in studies with other deer species, Rola et al (2021) observed that the IVM medium containing 5.0 µg/mL FSH, 100 µg/mL hCG and 1.0 µg/mL estradiol was efficient for maturation of brown brocket deer (Mazama gouazoubira) oocytes (64.5%).…”
Section: In Vitro Maturation Conditionsmentioning
confidence: 92%
“…In this species, it was observed that during the estrous season, the best IVM medium was supplemented with 10 μg/mL FSH, 1 μg/mL LH, 0.2 mM cysteamine, and 50 ng/mL EGF, while in the anestrous season, double these concentrations was more efficient (Yin et al, 2012). Additionally, based on the findings observed in studies with other deer species, Rola et al (2021) observed that the IVM medium containing 5.0 µg/mL FSH, 100 µg/mL hCG and 1.0 µg/mL estradiol was efficient for maturation of brown brocket deer (Mazama gouazoubira) oocytes (64.5%).…”
Section: In Vitro Maturation Conditionsmentioning
confidence: 92%
“…In O. virginianus, the kinetics of the nuclear progression of the oocytes was observed in vitro, and oocytes in the germinal vesicle stage were observed from 0 to 3 h. The maturation of the oocytes of M. gouazoubira collected by LOPU and matured for 24 h resulted in 64.52% of oocytes in MII. In addition, it was found that 14.2% of the oocytes were immature, 4.84% were degenerate, and 16.13% presented spontaneous activation by parthenogenesis [111].…”
Section: In Vitro Embryo Productionmentioning
confidence: 98%
“…In this protocol, CIDR ® was used for eight days with an intramuscular application of estradiol benzoate (25 mg) and the administration of eight doses of FSH (total of 130 mg) every 12 h from the fourth day until the seventh day. For M. gouazoubira, ovarian stimulation was considered satisfactory, and the average number of follicles observed after surgery was 17.07 ± 9.12 [111]. In M. americana, females from purebred crosses (buck and hind from the same cytotype) showed good follicular growth response.…”
Section: In Vitro Embryo Productionmentioning
confidence: 99%
See 1 more Smart Citation